Commodity-Based Analysis of Sea Toll Utilization: a Case Study of Salt and Seaweed Distribution in Sabu Raijua - Putri Dwi Kinanti Djahamouw; Desri Marfenita Halle Kore (Jurnal Impresi Indonesia, 2025)
The distribution of superior commodities from the archipelago is often constrained by limited infrastructure and high logistics costs. To answer these challenges, the government launched the Sea Toll program with the aim of reducing price disparities while opening up market access for local products. However, the effectiveness of Sea Tolls in remote areas still fluctuates, especially in supporting the sustainability of strategic commodity supply chains. This study examines the dynamics of the distribution of leading commodities—salt and seaweed—in Sabu Raijua Regency in the 2020–2025 period with the aim of analyzing the trend of sea toll utilization, identifying the factors causing fluctuations, and formulating a strengthening strategy. A mixed methods approach was used: quantitative analysis of 2020–2025 distribution data as well as qualitative analysis with fishbone and SWOT. The results of the study show that seaweed since 2021 has been completely dependent on non-Sea Toll ships, with fluctuating volumes and some of the proceeds being distributed informally, including bartering with rice or being sent directly to Makassar. On the other hand, the distribution of salt is relatively more stable and had made significant use of the Sea Toll in 2022 (42.7%) and 2025 (39.3%), although its contribution decreased in 2023–2024. The determining factors for the difference in distribution patterns between salt and seaweed include production scale, shelf life, logistics infrastructure, and the involvement of local actors. Field surveys found that salt ponds are managed by local governments with a profit-sharing system and by the private sector that has owned their own transport ships since 2014, thus strengthening the dominance of non-Sea Toll routes. This study concludes that the effectiveness of Sea Tolls is greatly influenced by commodity characteristics and local supply chain structures. The academic contribution of this research is to expand the discourse of marine transportation policy by emphasizing the importance of commodity-based approaches. Practically, the recommendations submitted include adjusting routes, strengthening logistics infrastructure, empowering farmer institutions, and downstreaming products to increase added value.